ANALISA CLOCK GENERATOR PADA RANGKAIAN POWER SUPPLY UNTUK APLIKASI TRIGER IC TTL DILABORATORIUM DIGITAL PROGRAM STUDI TEKNIK ELEKTRONIKA DI POLITEKNIK NEGERI MALANG - Hariyanto; Rosita Ferdiyana (Jurnal Teknik Ilmu dan Aplikasi, 2020)
The good performance of a clock generator circuit in the power supply for triger TTL IC is very influential on the success of the lab. A series. Therefore, the effectiveness of use must be adapted to its use in the practicum. To create a clock generator circuit as a source of pulses from a digital counter IC, a timer IC can be used. This pulse generator or clock generator can be used for clock sources in making counters up and down. Clock generators are often referred to as clock generators. The pulse generator in making the circuit is often used linear integrated circuit (IC: Integrated Circuit). A linear IC that is commonly used in general is usually the NE555 which is a timer IC. As a timer it can also be used analogically as a Clock Generator or pulse generator which can generally generate the frequency or time as needed.